2006
DOI: 10.1063/1.2337623
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of reorientational correlation functions of water at the water-lipid bilayer interface

Abstract: We studied the effects of confinement and the head group motion on the behavior of the reorientational correlation functions for water molecules at the water/lipid bilayer interface. The correlation functions were calculated from the data obtained from two molecular dynamics simulations: one with a flexible bilayer and the other with a frozen bilayer. In our present analysis the water molecules were separated into spatial regions according to their distance from the bilayer surface and into population groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 23 publications
10
38
1
Order By: Relevance
“…Some properties of biological membranes can be directly attributed to the characteristics of single phospholipid molecules. Due to their important role, phospholipids are the subject of numerous experimental and computational studies in recent decades [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some properties of biological membranes can be directly attributed to the characteristics of single phospholipid molecules. Due to their important role, phospholipids are the subject of numerous experimental and computational studies in recent decades [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have studied hydration water extensively, concluding that most of the perturbation induced by an interface extends only a few molecular layers 14. In an experiment, it is often difficult to separate the contribution of the interfacial water from the overwhelming background of bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of the water nanopool is 9 nm. Experimental and theoretical results have shown that only the first hydration layer around an interface or solute is substantially perturbed (20,(24)(25)(26)(27), so we can assume that the interfacial water is located primarily within a shell having a thickness of 0.28 nm (3), which is the approximate diameter of a water molecule. Calculating the volume of this shell and dividing it by the total volume of the micelle interior yields a fraction of 0.18.…”
mentioning
confidence: 99%